Genetic controls balancing excitatory and inhibitory synaptogenesis in neurodevelopmental disorder models - Gatto, Cheryl L.; Broadie, Kendal (Frontiers in Synaptic Neuroscience, 2010)
Proper brain function requires stringent balance of excitatory and inhibitory synapse formation during neural circuit assembly. Mutation of genes that normally sculpt and maintain this balance results in severe dysfunction, causing neurodevelopmental disorders including autism, epilepsy and Rett syndrome. Such mutations may result in defective architectural structuring of synaptic connections, molecular assembly of synapses and/or functional synaptogenesis. The affected genes often encode synaptic components directly, but also include regulators that secondarily mediate the synthesis or assembly of synaptic proteins. The prime example is Fragile X syndrome (FXS), the leading heritable cause of both intellectual disability and autism spectrum disorders. FXS results from loss of mRNA-binding FMRP, which regulates synaptic transcript trafficking, stability and translation in activity-dependent synaptogenesis and plasticity mechanisms. Genetic models of FXS exhibit striking excitatory and inhibitory synapse imbalance, associated with impaired cognitive and social interaction behaviors. Downstream of translation control, a number of specific synaptic proteins regulate excitatory versus inhibitory synaptogenesis, independently or combinatorially, and loss of these proteins is also linked to disrupted neurodevelopment. The current effort is to define the cascade of events linking transcription, translation and the role of specific synaptic proteins in the maintenance of excitatory versus inhibitory synapses during neural circuit formation. This focus includes mechanisms that fine-tune excitation and inhibition during the refinement of functional synaptic circuits, and later modulate this balance throughout life. The use of powerful new genetic models has begun to shed light on the mechanistic bases of excitation/inhibition imbalance for a range of neurodevelopmental disease states.